2016
DOI: 10.1016/j.ijsu.2016.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Visceral obesity, muscle mass and outcome in rectal cancer surgery after neo-adjuvant chemo-radiation

Abstract: It appears that VO is associated with co-morbidity and poor outcome in rectal cancer patients. Using different cutoff values for VO different associations with outcome were found. SMA increased during chemoradiation, a phenomenon that remains to be explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 27 publications
3
39
1
Order By: Relevance
“…Increased adipose tissue compartments, but not BMI or body weight, were positively correlated with the length of hospital stay, which was also seen by Tsujinaka et al[25], Chern et al[29], and Heus et al[28], who also observed a prolonged hospital stay in obese. Regarding surgery duration, weight, BMI, and all adipose tissue compartments were positively correlated, probably due to aggravated surgical conditions with reduced visibility.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Increased adipose tissue compartments, but not BMI or body weight, were positively correlated with the length of hospital stay, which was also seen by Tsujinaka et al[25], Chern et al[29], and Heus et al[28], who also observed a prolonged hospital stay in obese. Regarding surgery duration, weight, BMI, and all adipose tissue compartments were positively correlated, probably due to aggravated surgical conditions with reduced visibility.…”
Section: Discussionsupporting
confidence: 73%
“…There was no significant correlation of blood loss with any adipose tissue compartment as well as weight or BMI. In contrast, in a study by Heus et al [28], high VAT was associated with high perioperative blood loss.…”
Section: Discussionmentioning
confidence: 74%
“…A few previous studies have included stage IV colorectal cancers with hepatic metastasis . One study included rectal cancer surgical patients after neoadjuvant chemoradiation therapy, but it only analysed perioperative outcomes without long‐term oncologic outcomes …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, 100 and 130 cm 2 were used as cut‐offs . In our study, we defined visceral obesity with area of visceral fat >100 cm 2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation